บทวิเคราะห์ปัญหาทางนิเวศนวิทยาของยูคาลิปตัส - สุวรรณาภินันท์, วิสุทธิ์ (วารสารวนศาสตร์ไทย, 2022)
The analytical reviews on ecological problems of planting Eucalyptus in Thailand is presented. The problems are included those of soil, water, allelopathy and weediness. The analyses are based on the published research articles together with actual evidences of planting Eucalyptus for nearly four decades in Thailand. For readers' verdict, the analyses are attempted by comparing the effects of planting the problem species to those of other tree species or to those of natural stands in some cases. It appears that the beneficial effects of planting Eucalyptus in Thailand overweigh the proposed adverse effects. There are no grounds for believing that planting the eucalypts may cause any adverse effects on the soils and the sites. Eucalyptus can be planted in Thailand without any fears of site deterioration.